2012
DOI: 10.4025/actasciagron.v34i3.13942
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the allocation of phytomass in soybean and bean and its potential role in biological nitrogen fixation

Abstract: Soybean is a self-sufficient specie in nitrogen acquisition due to their efficient association with diazotrophs. Unlike bean, which requires nitrogen supplementation, soybean is not dependent on nitrogen fertilization. This interspecies difference may be related to the allocation pattern of photosynthates during their growth cycles. Distinct from soybean, common bean cannot maintain their active nodules until the end of their growth cycle due to the unavailability of photosynthates in their roots after floweri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…If reinvestment of gain from one symbiont into the complementary symbiont is necessary for realization of synergism, then there may be an additional lag in realization of this benefit. Annual legumes can have very short life‐spans and investment in roots can be reduced with initiation of flowering (Portes & Araújo, 2012 ), when plants begin preferentially allocating carbon to flower and fruit production, potentially reducing the opportunity to realize synergism compared to perennial legumes.…”
Section: Introductionmentioning
confidence: 99%
“…If reinvestment of gain from one symbiont into the complementary symbiont is necessary for realization of synergism, then there may be an additional lag in realization of this benefit. Annual legumes can have very short life‐spans and investment in roots can be reduced with initiation of flowering (Portes & Araújo, 2012 ), when plants begin preferentially allocating carbon to flower and fruit production, potentially reducing the opportunity to realize synergism compared to perennial legumes.…”
Section: Introductionmentioning
confidence: 99%
“…Araújo & Teixeira (2008), in two field experiments, observed that the grain yield of common bean cultivars did not correlate with shoot mass exhibited at the flowering or pod setting stages, whereas grain yield correlated with shoot mass at the beginning of the pod filling and mid-pod filling stages, concluding that the yield potential of different common bean cultivars is not intrinsically associated with the vegetative vigor at flowering. The nutrient budget of common bean cultivars grown in the field also demonstrated that acquisition of N and P during early pod-filling is rather significant in fulfilling seed demand, whereas during late pod-filling, nutrient remobilization within the plant assumes more relevance to the crop budget (Araújo et al, 2012). Therefore, genotypic selection for improved growth and nutrient acquisition within common bean cultivars should be performed preferentially during the early pod-filling stages, in which the growth and yield potentials of a specific genotype are likely to be fully expressed.…”
Section: Perspectives Of Selection For Root Traitsmentioning
confidence: 99%
“…Portes & Araújo (2012), comparing common bean and soybean in terms of biomass allocation among plant tissues, noticed that during reproductive stages bean plants invested preferentially in pod growth in detriment to the root system and other vegetative organs. Notably, genotypes of groups II and III showed much more intense growth of basal and lateral roots between the two times of harvest than the genotypes of groups I and IV (Table 3).…”
Section: Genotypic Variabilitymentioning
confidence: 99%
“…Soybeans are a valuable source of protein and oil, containing essential free amino acids and fatty acids, as well as other nutrients such as isoflavones, phytosterols and saponins (isoflavone, phytosterol, and saponins) [3,4]. Cultivation of soybean plants does not require large doses of nitrogen, which is possible thanks to the symbiosis of those plants with nodule bacteria (Bradyrhizobium japonicum) present in the root nodules, assimilating atmospheric nitrogen (N 2 ) [5,6]. The productivity of soybeans is determined by the interactions between the selection of the appropriate genotype of a cultivar and the environment and the Agronomy 2021, 11, 403 2 of 18 method of cultivation of that species [7].…”
Section: Introductionmentioning
confidence: 99%